Obscure gastrointestinal bleeding caused by congenital enteropathy in a Chinese young child-a case report - Fang, Youhong (BMC Pediatr, 2020)
BACKGROUND: SLCO2A1 was recently reported to cause nonspecific ulcers at small bowel, it was named as chronic enteropathy associated with SLCO2A1 (CEAS). It was rarely reported beyond the Japanese population. CASE PRESENTATION: A 4-year-5-month old girl presented with intractable anemia since 1-year-3-month. Her stool occult blood test was positive and the result of esophagogastroduodenoscopy and colonoscopy were normal. She was considered as obscure gastrointestinal bleeding. The magnetic resonance enterography and ultrasound of small intestinal revealed segmental thickening of small bowel. The capsule endoscopy detected ulcers, erosion and slightly stenosis near the site of junction of jejunum and ileum. She was considered chronic non-specific multiple ulcers of the small intestine and was advised to have whole exon sequencing. She was treated with exclusive enteral nutrition and iron supplement for two months. However, she was not responsive to this treatment, then she had three doses of infliximab. At the same time, the next-generation sequencing of this patient revealed two novel compound heterozygous mutations in SLCO2A1. She was diagnosed with CEAS and was treated with oral mercaptopurine. Her hemoglobin level was stable and the serum albumin level was slightly decreased during the follow up. CONCLUSION: CEAS may present as nonspecific small bowel ulcers, and misinterpret as small bowel Crohn’s disease. Genetic tests may help with the precise diagnosis of small bowel ulcers.